Utilization of galactomannan from Gleditsia triacanthos in polysaccharide-based films : effects of interactions between film constituents on film properties - Cerqueira, M. A. (2013)
The objective of this work was to evaluate the effect of the concentrations of Gleditsia triacanthos galactomannan and glycerol and the presence of corn oil in the physical properties of edible films. The influence of interactions between those constituents on films' permeability to gases (water vapour, CO2 and O2), solubility in water, mechanical properties and colour was evaluated. The effects of those variables were analysed according to a 23 factorial design; regression coefficients were used to understand the influence of each variable (factor) on the studied properties, and a multifactor model was developed. Results show that galactomannan concentration is the most significant factor affecting the studied properties; moreover, the increase of plasticizer concentration and the presence of oil showed to be the most influent in the particular cases of solubility and transport properties (water vapour permeability and O2 permeability), respectively. These results show that galactomannan films' properties can be tailored to allow their use as alternative to non-biodegradable, non-edible packaging materials.